Corporate Social Responsibility as a Determinant of Competitiveness in Supermarkets - Pardo Rozo, Yelly Yamparli; Carvajal Valderrama, Gabriela; Perdomo Carvajal , Alexandra (Mercados y Negocios, 2024)
The research aimed to analyze the contribution of Corporate Social Responsibility (CSR) to the competitiveness of supermarkets in Florencia, Caquetá in southern Colombia. In a sample of six supermarkets, a self-assessment survey of CSR and competitiveness variables was carried out for 2021 to 2022, consisting of six dimensions: values and ethical principles, responsible marketing, economy and finance, social commitment, quality of working life, and environment. The tool makes it possible to measure the commitment of the organization’s CSR activities to competitiveness. The environment is the dimension with the lowest score and contribution to competitiveness in the dimensions evaluated in the supermarkets (2.0 on a scale of 0.0 - 3.0). According to the correlation analysis, there is a relationship between CSR and competitive position. Awareness-raising and training actions aimed at stakeholders are proposed.